The problem of forming skills from academic writing for future programmers - Artur Emiratli; Mykola Marchuk; Kateryna Osadcha (Ukrainian Journal of Educational Studies and Information Technology, 2017)
The ability to write a scientific publications and works plays an important role in science. Different aspects of teaching academic writing were considered in the writings of scientists, in particular the peculiarities of writing skills and skills of foreign language students, approaches to the formation of academic writing skills in English language classes at medical universities, peculiarities of the methodology of teaching English writing (practical, academic and creative), content training courses on the formation of language competence from academic writing at separate stages of study (bachelor's, master's and doctoral studies), methods of teaching students writing in English. However, the features of academic writing in the field of computer science in the national scientific thought were considered insufficient. In the article, based on the analysis of theoretical studies on academic writing (J. Zobel, I. B. Korotkina) practical experience of forming an academic writing for future specialists (T. Babenko, L. Sazanovych), in particular future IT specialists (V. О. Safonov, O. S. Synekop), an understanding of the concept of "academic writing" is presented and the content component of the methodology of academic writing for future programmers is developed. Offered on the first and fourth courses to introduce elements of teaching academic writing future programmers in learning the disciplines "Introduction in specialty programmer" and "Methods of writing the diploma project". This approach will provide empiricism in research in the field of information technology and will prepare students for in-depth studies in a magistracy and postgraduate study, will allow us to teach future programmers to plan, conduct and describe research that involves the formulation of research questions, theory, data analysis (using both quantitative and qualitative methods), preparation of evidence, evaluation of the validity and publication. They will learn to use research methods, which are used for human interaction with computer technology: a controlled experiment, testing the software, efficiency of the calculation algorithms, the calculation of the economic efficiency of the developed software. In addition, we consider it appropriate to focus on the fact that despite the fact that at first glance, a programmer's professional activity has little to do with the writing, it is still an essential component of their daily work. In the future prospects of the study, it is planned to conduct an experimental study in order to find out the effectiveness of the proposed methodology of forming academic writing skills from future programmers.